Efektivitas Metode Komunikasi Antar Pribadi (KAP) dalam Meningkatkan Perubahan Perilaku Ibu dalam Penanganan Stunting pada Balita: Sebuah Tinjauan Literatur - Desi Siswanty; Erika Erika; Reni Zulfitri (Universitas Pahlawan Tuanku Tambusai, 2025)
Abstract Stunting in toddlers is a health problem with long-term effects on child growth and development. The Interpersonal Communication (IPC) approach is believed to improve mothers' understanding and behavioral change in managing stunting. This study aimed to review the effectiveness of the IPC method in influencing maternal behavior regarding stunting management. The method used was a literature review by searching scientific articles from ScienceDirect, PubMed, and Google Scholar databases. A total of 11 relevant articles from countries such as Ethiopia, Tanzania, Afghanistan, and Indonesia were analyzed to evaluate the impact of IPC interventions. The findings indicate that IPC is effective in enhancing knowledge, compliance, and positive maternal behavior towards nutrition and child care practices. The success of IPC is influenced by communication quality, trust between communicator and communicant, and message relevance. In conclusion, IPC is a potentially effective strategy to support stunting intervention programs, especially by strengthening mothers’ roles in child nutrition care. Keywords: Stunting, Interpersonal Communication, Maternal Behavior, Child Nutrition, Prevention